1: déterminer les signe de chaque expression,puis la calculer;

A= (-1) x (-5) x (-7) x (-2)
B= 7 x (-3) x (-7) x 3
C= (-15) x( -0,1) x 4 x (-6)

2
A = 5 x (-7) x (-2)
pk tu marque pas sa dans le truc reponcer
=-35 x (-2) = 70

Réponses

Meilleure réponse !
2014-09-15T20:29:10+02:00
1: Déterminer les signe de chaque expression,puis la calculer :
A = (- 1) x (- 5) x (- 7) x (- 2)
A = 5 x 14
A = 70

B = 7 x (- 3) x (- 7) x 3
B = - 21 x - 21
B = 441

C = (- 15) x (- 0,1) x 4 x (- 6)

C = 1,5 x - 24
C = - 36
2014-09-15T20:30:06+02:00
A =70
B= -21 x (-7) x 3
= 147 x 3
= 441

C = 1,5 x 4x(-6)
= 6 x(-6)
= -36